Independent and inclusive economic: SAGATA's micro-enterprise empowers disability local crafters in Yogyakarta - Amrullah, Muhammad Karim (Universitas Negeri Yogyakarta, 2024)
SDGs Goal 8 aims to promote decent work and economic growth. The government must guarantee inclusive economic growth and development for disabilities. An inclusive economic environment should be guaranteed, as mandated by the Disabilities, Employment, and Job Creation Law, which also accommodates MSMEs. The tourism and creative industries are independent economic sectors contributing to DI Yogyakarta's image and revenues. As an independent local economic actor and an MSMEs Yogyakarta-based, Sagata creates an inclusive environment. Sagata empowers local people with disabilities as craftsmen workers, showing inclusivity in recruitment and acceptance of disabilities. The method used in this research is normative-empirical legal research. Data were collected using an in-depth literature study. Data analysis uses Miles and Huberman qualitative data analysis. It is important to understand the Sagata's efforts to realise the mandates. The findings show that Sagata is important in realising economic development and supporting efforts to implement the SDGs and related laws. Related to civic engagement value, these show that marginalised people can contribute even on a small economic scale.